Hydrological Impacts of Climate Change (Rainfall and Temperature) and Characterization of Future Drought in the Aga Foua Djilas Watershed - Dione, Philippe Malick; Faye, Cheikh; Sadio, Cheikh Abdoul Aziz Sy (CV. Literasi Indonesia, 2023)
Studying climate change's impact on runoff and drought is crucial for sustainable society and ecosystems. The extent of drought evolution and how droughts would affect society and the environment are not sufficiently considered in Senegal. This study assesses hydrological impacts and future drought using three global climate models (ACCESS-ESM1-5, BCC-CSM2-MR, and MRI-ESM2-0) as part of the Coupled Model Intercomparison Project (CMIP6) in the Aga-Foua-Djilas Basin. To this end, the hydrological impacts of climate change over 20-year periods (2021-2040; 2041-2060; 2061-2080; 2081-2100) at a resolution of 2.5 under four emission scenarios (SSP 126; 245; 370; 585), were investigated, and the drought characteristics are shown below, the SSP 245 and 585 scenarios over the 2021-2100 period. The results highlight a decrease in runoff potential given the drop in rainfall, which fell from 25.2 mm over the 2021-2040 period and under SSP 126 to 2.4 mm towards the end of the century (2081-2100) and under the SSP 585 scenario, changes in the standardized precipitation index (SPI) and the standardized precipitation and evapotranspiration index (SPEI) were first compared, and the SPEI showed larger changes due to its inclusion of temperature effects. The drought zone in the basin is likely to increase at the end of the 21st century with values approaching 80% for SPI and 90% for SPEI under the SSP 245 and SSP 585 scenarios if drought mitigation and adaptation mechanisms are inadequate. The results provide important guidance for improving the identification of causes, minimizing impacts, and building resilience to droughts in Senegal.